2005
DOI: 10.1016/j.chb.2003.11.008
|View full text |Cite
|
Sign up to set email alerts
|

An overview of online trust: Concepts, elements, and implications

Abstract: Lack of trust has been repeatedly identified as one of the most formidable barriers to people for engaging in e-commerce, involving transactions in which financial and personal information is submitted to merchants via the Internet. The future of e-commerce is tenuous without a general climate of online trust. Building consumer trust on the Internet presents a challenge for online merchants and is a research topic of increasing interest and importance. This paper provides an overview of the nature and concepts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
419
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(441 citation statements)
references
References 43 publications
12
419
1
9
Order By: Relevance
“…In turn, they found that product quality affected purchase intentions. These findings are similar to the ideas of Wang and Emurian (2005), who suggest that four design factors (i.e., graphic design, structural design, content design, and social-cue design) have a prominent role in creating a quality Volume 8…”
Section: Website Credibility and Qualitysupporting
confidence: 86%
See 1 more Smart Citation
“…In turn, they found that product quality affected purchase intentions. These findings are similar to the ideas of Wang and Emurian (2005), who suggest that four design factors (i.e., graphic design, structural design, content design, and social-cue design) have a prominent role in creating a quality Volume 8…”
Section: Website Credibility and Qualitysupporting
confidence: 86%
“…Thus, it might be possible to integrate these factors into systems to do real-time evaluations of website visitors. Nevertheless, even without these sophisticated technologies, the fact that the type of interpretations that our subjects noted were consistent with the four design factors that Wang and Emurian (2005) note suggests that there are also more straightforward design principles that one can employ to influence what people notice and how they interpret what they are looking at as they make evaluations of credibility. Our results are consistent with these and similar findings that show that building a website that, for lack of a better way of saying it, looks credible can influence credibility.…”
Section: Volume 8 Issuementioning
confidence: 69%
“…There are four consumer concerns that differentiate an online from in-store transaction [20]: (a) increased risk, (b) the resulting trustor and trustee relationship, (c) security concerns about financial information, and (d) subjective privacy concerns.…”
Section: Consumer Concernsmentioning
confidence: 99%
“…This information includes fast product search, value-added, and customized information (Liang & Lai, 2002). Additionally, website structure is defined as overall information of online companies and convenience of displayed information on website (Wang & Emurian, 2005). This website's structure will reflect the customer's view of website information, products, or services (Nielsen, 1999).…”
Section: Literature Review E-loyaltymentioning
confidence: 99%